Important Questions and Answers that - Shape the Future of JTR and which provide Core Insights of what JTR is all about. - Zhang Jianhui (Journal of Transgenics, 2018)
An editorial in Q&A format outlines the journal’s aims, editorial standards, and thematic priorities, inviting contributions that advance transgenic science and applications.